2020
DOI: 10.1021/acs.jafc.9b08083
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Mannoproteins from Yeast Affect Salivary Protein–Flavanol Interactions through Different Molecular Mechanisms

Abstract: It is known that interactions between wine flavanols and salivary proline-rich proteins (PRPs) are one of the main factors responsible for wine astringency. The addition of commercial yeast mannoproteins (MPs) to wines has been pointed to as a possible tool to modulate the excessive astringency due to a lack of phenolic maturity at harvest time that might occur as a consequence of global climate change. The aim of this work was to study by isothermal titration calorimetry and molecular dynamics simulation the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 50 publications
(98 reference statements)
6
36
0
Order By: Relevance
“…Mannoproteins (MPs), a group of polysaccharides with variable size and composition from the cell wall of yeast, were proved to effectively mitigate the astringency of red wine (Rinaldi, Coppola, & Moio, 2019). As demonstrated by Manjón, Brás, García‐Estévez, and Escribano‐Bailón (2020), MPs with different compositional characteristics showed diverse astringency modulating effects by different mechanisms. Specifically, MPs could exert the effects by forming ternary aggregates with grape seed flavanols and SPs, called associative mechanism, and preventing the interactions between flavanols and SPs via binding to flavanols and interacting with SPs, called competitive mechanism.…”
Section: Emerging Mitigation Approaches To Astringency Triggered By Pmentioning
confidence: 89%
“…Mannoproteins (MPs), a group of polysaccharides with variable size and composition from the cell wall of yeast, were proved to effectively mitigate the astringency of red wine (Rinaldi, Coppola, & Moio, 2019). As demonstrated by Manjón, Brás, García‐Estévez, and Escribano‐Bailón (2020), MPs with different compositional characteristics showed diverse astringency modulating effects by different mechanisms. Specifically, MPs could exert the effects by forming ternary aggregates with grape seed flavanols and SPs, called associative mechanism, and preventing the interactions between flavanols and SPs via binding to flavanols and interacting with SPs, called competitive mechanism.…”
Section: Emerging Mitigation Approaches To Astringency Triggered By Pmentioning
confidence: 89%
“…Another research on the molecular mechanisms by which polysaccharides can affect protein-tannin interactions was developed by Manjón and coworkers [156]. These authors studied the molecular mechanisms by which commercial MPs could modulate astringency elicited by tannins through ITC and molecular dynamics simulation.…”
Section: Polysaccharide Effects On Astringencymentioning
confidence: 99%
“…The results obtained indicate that MPs could affect astringency by the formation of ternary aggregates with different solubilities or by preventing flavanol-PRPs interactions by a competitive mechanism. This MPs effect is different among the several MPs used, depending on the size and the compositional characteristic of the MP fraction [156]. The effect of wine polysaccharides on the interaction between wine flavan-3-ols and BSA was also studied at the molecular level by another research approach using fluorescence [63].…”
Section: Polysaccharide Effects On Astringencymentioning
confidence: 99%
“…35% of total wine polysaccharides . These polysaccharides are glycoproteins released from the yeast cell wall during alcoholic fermentation and autolysis, and their influence on sensory quality of wines has been widely reported. , Furthermore, a very recent study carried out by Manjón and co-workers demonstrated, for the first time, a relationship between the compositional characteristics of mannoproteins and their differences in the mechanisms of action toward astringency modulation.…”
Section: Introductionmentioning
confidence: 99%